Does Inflation Targeting Matter for Output Growth? Evidence from Industrial and Emerging Economies - Mollick, Andre Varella; Cabral, Rene; Carneiro, Francisco G. (2012)
This paper examines the effects of inflation targeting (IT) on output growth over the "globalization years" of 1986-2004. Employing static panel data methods that control for traditional growth determinants, trade openness and financial globalization, the paper finds that the adoption of a fully fledged IT regime results in higher output income per capita for industrial and emerging economies. However, under dynamic model specifications, the estimated long-run output impact of inflation targeting for emerging market economies is found to be lower than in the case of static models. We argue that this might be due to the long lags until the full effects of greater credibility are felt in the real economy and the fact that emerging market economies adopted the regime much later than industrial economies.